Spectral Signatures of Protonated Noble Gas Clusters of Ne, Ar, Kr, and Xe: From Monomers to Trimers - Jake A. Tan; Jer-Lai Kuo (Molecules, 2022)
The structures and spectral features of protonated noble gas clusters are examined using a first principles approach. Protonated noble gas monomers (NgH+) and dimers (NgH+Ng) have a linear structure, while the protonated noble gas trimers (Ng3H+) can have a T-shaped or linear structure. Successive binding energies for these complexes are calculated at the CCSD(T)/CBS level of theory. Anharmonic simulations for the dimers and trimers unveil interesting spectral features. The symmetric NgH+Ng are charactized by a set of progression bands, which involves one quantum of the asymmetric Ng-H+ stretch with multiple quanta of the symmetric Ng-H+ stretch. Such a spectral signature is very robust and is predicted to be observed in both T-shaped and linear isomers of Ng3H+. Meanwhile, for selected asymmetric NgH+Ng’, a Fermi resonance interaction involving the first overtone of the proton bend with the proton stretch is predicted to occur in ArH+Kr and XeH+Kr.